1983
DOI: 10.1210/endo-113-3-921
|View full text |Cite
|
Sign up to set email alerts
|

Propylthiouracil (PTU) Pharmacology in the Rat,II. Effects of PTU on Thyroid Function*

Abstract: Using a sensitive and specific RIA for propylthiouracil (PTU), we examined the effects of short term (1 week) and long term (1 month) PTU treatment on thyroid function in the rat, and correlated changes in thyroid function with serum and thyroid PTU levels. After 1 week, dose-dependent decreases in thyroid PBI, serum T4, and serum T3 were observed, with concomitant elevations in the serum rT3 to T4 ratio and serum TSH. Fifty percent suppression of thyroid PBI occurred at a PTU concentration in the drinking wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
1
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 29 publications
8
30
1
2
Order By: Relevance
“…Hypothyroid condition showed an appreciable decline in both serum T4 and T3 level in rats in a usual way as found by other investigators (Larsen and Frumess 1977;Leonard et al 1981;Cooper et al 1983). Although it has been shown earlier that in hypothyroid condition, the whole brain, or different regions of the brain, maintain similar levels of T 3 compared to the euthyroid control rats through increased activity of 5'-deiodinase type II (S'D-II), and corresponding high fractional rate of T4 to T3 conversion (Obregon et al 1978;Vigoroux et al 1979;Crantz and Larsen 1980;Kaplan and Yaskoski 1980;Leonard et al 1981;Leonard et al 1984;Morreale de Escobar et al 1988;St Germain et al 1988;Escobar del Rey 1989;Serrano-Lozano et al 1991), insufficient evidence is available except for a few recent reports (Sarkar and Ray 1992b;Mason et al 1993) to quantitate the synaptosomal concentration of thyroid hormone.…”
Section: Synaptosomal Concentrations Of T 4 and Tsupporting
confidence: 84%
“…Hypothyroid condition showed an appreciable decline in both serum T4 and T3 level in rats in a usual way as found by other investigators (Larsen and Frumess 1977;Leonard et al 1981;Cooper et al 1983). Although it has been shown earlier that in hypothyroid condition, the whole brain, or different regions of the brain, maintain similar levels of T 3 compared to the euthyroid control rats through increased activity of 5'-deiodinase type II (S'D-II), and corresponding high fractional rate of T4 to T3 conversion (Obregon et al 1978;Vigoroux et al 1979;Crantz and Larsen 1980;Kaplan and Yaskoski 1980;Leonard et al 1981;Leonard et al 1984;Morreale de Escobar et al 1988;St Germain et al 1988;Escobar del Rey 1989;Serrano-Lozano et al 1991), insufficient evidence is available except for a few recent reports (Sarkar and Ray 1992b;Mason et al 1993) to quantitate the synaptosomal concentration of thyroid hormone.…”
Section: Synaptosomal Concentrations Of T 4 and Tsupporting
confidence: 84%
“…In our study, the alterations in serum total T4 and T3 levels observed on Day '2' and Day '20' of PTU treatment were typical of peripheral hypothyroidism involving hypothalamo-pituitary-thyroid axis [6,16]. There were no changes in serum total T4 and T3 concentrations when the dopaminergic agonist, bromocryptine (BROMO), and antagonist, haloperidol (HALO), were treated to animals, either alone or in combination with PTU, on Day '2' and Day '20'.…”
Section: Discussionsupporting
confidence: 53%
“…The control group received drinking water not containing PTU. This regimen has been used previously by others and has been shown to be effective in inhibiting thyroid hormone synthesis without influencing litter size or viability (6). The procedures and dosage of PTU were identical to those used in previously reported full-term newborn rat studies from our laboratories [calculated maternal dose of PTU .-: 30 mglkgld (approximately twice the orally administered clinical dosage)].…”
Section: Animals and Treatmentmentioning
confidence: 99%